Digital Libraries: Mission Accomplished? - Bainbridge, David (Journal of Information and Knowledge, 2019)
This article is the first in a series of three publications that reflects on the boundaries and perceptions of what we think of when we hear the term Digital Libraries, as substantiated through our mainstream digital library systems. In this first article we lay the groundwork, concentrating on detailing the capabilities of established digital libraries, as a point of reference. We present a range of examples and highlight the commonalities that occur despite dealing with diverse topics and subject matter. We then go on to detail generalized forms of digital library that occur and discuss the software architecture behind them.